Ultra Wideband Dipole Antenna - Bakhrakh, L.D.; Los', V.F.; Shamanov, A.N. (Радиофизика и радиоастрономия, 2002)
This paper considers the antenna-feeder device which helps to realize a new method of antenna excitation. This method enables to transfer dipole antennas into the ultra-wideband category. The paper also demonstrates the experimental characteristics. В этой статье рассматривается антенно-фидерное устройство, в котором реализован новый метод возбуждения антенны. Это позволяет использовать дипольную антенну в качестве сверхширокополосной. У цій статті розглянуто антенно-фідерний пристрій, у якому реалізовано новий метод збудження антени. Це дозволяє використовувати дипольну антенну у якості надширокосмугової.